Erosion and abrasion on dental structures undergoing at-home bleaching - Tarquinio SBC; Botero T; Dantas RVF; Sarmento HR; Meireles SS; Demarco FF (Dove Medical Press, 2011)
Flávio Fernando Demarco1, Sônia Saeger Meireles2, Hugo Ramalho Sarmento1, Raquel Venâncio Fernandes Dantas1, Tatiana Botero3, Sandra Beatriz Chaves Tarquinio11Graduate Program in Dentistry, School of Dentistry, Federal University of Pelotas, Brazil; 2Department of Operative Dentistry, Federal University of Paraíba, Brazil; 3Cariology, Restorative Science, and Endodontics Department, School of Dentistry, University of Michigan, MI, USAAbstract: This review investigates erosion and abrasion in dental structures undergoing at-home bleaching. Dental erosion is a multifactorial condition that may be idiopathic or caused by a known acid source. Some bleaching agents have a pH lower than the critical level, which can cause changes in the enamel mineral content. Investigations have shown that at-home tooth bleaching with low concentrations of hydrogen or carbamide peroxide have no significant damaging effects on enamel and dentin surface properties. Most studies where erosion was observed were in vitro. Even though the treatment may cause side effects like sensitivity and gingival irritation, these usually disappear at the end of treatment. Considering the literature reviewed, we conclude that tooth bleaching agents based on hydrogen or carbamide peroxide have no clinically significant influence on enamel/dentin mineral loss caused by erosion or abrasion. Furthermore, the treatment is tolerable and safe, and any adverse effects can be easily reversed and controlled.Keywords: peroxide, tooth bleaching, enamel, dentin, erosion, abrasion